Towards a Global History of Domestic and Caregiving Workers - Smith, Julia (Labour / Le Travail, 2017)
This article reviews the book, "Towards a Global History of Domestic and Caregiving Workers," edited by Dirk Hoerder, Elise van Nederveen Meerkerk, and Silke Neunsinger.